Interview with Luis Carlos Rodrigo Prado: Tax stability agreements and their impact on mining investment - Feijoo, Raúl (2014)
The interview focuses mainly on the theme of contracts Tax stability. thus, the author shows how its development has been in our system in recent years related to mining investment in our country and from the General Mining Act. He also takes a position with regard to measures to promote investment presented by the Government. Finally, the author emphasizes the importance of stability contracts primarily to provide certainty to investors.